Empowering Regional Economies through Sharia Finance: The Strategic Role of BPRS Bhakti Sumekar - Farisul Haq (Assyarikah: Journal of Islamic Economic Business, 2025)
This study aims to analyze the role of Bank Perekonomian Rakyat Syariah or BPRS Bhakti Sumekar Perseroda in supporting regional economic development in Sumenep Regency. This research uses a qualitative descriptive approach based on secondary data from the 2024 financial report of BPRS Bhakti Sumekar, relevant regulations, and supporting literature. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that BPRS Bhakti Sumekar plays a strategic role as an Islamic financial institution that distributes sharia-based financing to the real sector and as a regionally owned enterprise that contributes to Local Original Revenue. In 2024, BPRS Bhakti Sumekar collected IDR 829.33 billion in third-party funds, distributed IDR 651.57 billion in financing, recorded IDR 11.07 billion in net profit, and paid IDR 5.59 billion in regional dividends. In addition, the bank allocated IDR 868 million in CSR funds to support education, health, economic empowerment, social assistance, and religious outreach programs. These findings show that BPRS Bhakti Sumekar serves as a regional financial instrument that supports the real sector, regional revenue, and community welfare in Sumenep Regency.